Peran Sukuk Sebagai Penguat APBN - Rizki Romadhoni Saputra; Fayza Azzahra; Syahna Nur Hafizhya (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Infrastructure development is a key pillar in driving inclusive and sustainable national economic growth. However, budget constraints and dependence on foreign debt require efficient financing innovation. This study aims to examine the government's policy in the 2023 State Budget (APBN) on the inclusion of sharia financing through sukuk instruments in strategic infrastructure development. This study uses a descriptive qualitative approach combined with public policy analysis methods based on secondary data from official documents and academic literature. The results of the analysis show that national sharia bonds, especially project-based sharia bonds (PBS), have made a significant contribution to financing national infrastructure projects, including financing environmentally friendly projects through green sharia bonds. The total sukuk outstanding reached IDR1,344.35 trillion in 2023, reflecting the strategic role of sukuk in supporting sustainable, efficient, and sharia-compliant financing. These results indicate that the inclusion of sukuk in the APBN not only expands public and investor participation, but also increases fiscal stability and supports the country's economic transformation. Keywords: Infrastructure; Sharia Financing; Sukuk; State Budget 2023. Abstrak Pembangunan infrastruktur merupakan pilar utama dalam mendorong pertumbuhan ekonomi nasional yang inklusif dan berkelanjutan. Namun, keterbatasan anggaran dan ketergantungan pada utang luar negeri menuntut inovasi pembiayaan yang efisien. Penelitian ini bertujuan untuk mengkaji kebijakan pemerintah dalam Anggaran Pendapatan dan Belanja Negara (APBN) 2023 tentang penyertaan pembiayaan syariah melalui instrumen sukuk dalam pembangunan infrastruktur strategis. Penelitian ini menggunakan pendekatan kualitatif deskriptif yang dipadukan dengan metode analisis kebijakan publik berdasarkan data sekunder dari dokumen resmi dan literatur akademis. Hasil analisis menunjukkan bahwa obligasi syariah nasional, khususnya obligasi syariah berbasis proyek (PBS), telah memberikan kontribusi yang signifikan terhadap pembiayaan proyek infrastruktur nasional, termasuk pembiayaan proyek ramah lingkungan melalui obligasi syariah hijau. Total sukuk yang beredar mencapai Rp1.344,35 triliun pada tahun 2023, mencerminkan peran strategis sukuk dalam mendukung pembiayaan yang berkelanjutan, efisien, dan sesuai dengan prinsip syariah. Hasil ini menunjukkan bahwa masuknya sukuk dalam APBN tidak hanya memperluas partisipasi publik dan investor, tetapi juga meningkatkan stabilitas fiskal dan mendukung transformasi ekonomi negara. Kata kunci: APBN 2023; Infrastruktur; Pembiayaan Syariah; Sukuk.